A Bullet for Señor Cobos: Anarchy in the Galapagos - Jamieson, Ross W. (Journal of Contemporary Archaeology, 2019)
From 1878-1904 the El Progreso Hacienda was run by Manuel J. Cobos on the island of San Cristóbal in the Galapagos. Cobos was shot by his own workers in 1904. This paper explores the relationship between anarchy, banditry, and modern firearms in this unique rural setting at the turn of the 20th century.